Adverse Cerebral Outcomes after Coronary Artery Bypass Surgery—More Than a Decade of Experience in a Single Center - Loberman, Dan; Consalvi, Carrie; Healey, Allison; Rivera, Bridget; Poulin, Katherine; Mohr, Rephael; Ziv-Baran, Tomer (The Thoracic and Cardiovascular Surgeon, 2018)
Background Nonfatal strokes, transient ischemic attacks (TIAs), and reversible ischemic neurological deficits (RIND) after elective coronary artery bypass grafting (CABG) are devastating clinical problems. The anesthesiologist, surgical and intensive care teams in a community hospital adopted a strategy developed in an effort to minimize these adverse outcome events.The purpose of this study is to determine the incidence of and predictors for perioperative adverse neurologic events.Methods A historical cohort study of 1,108 consecutive CABG patients operated between 2002 and 2014. Outcomes were defined as (1) a new neurologic damage (a new stroke, TIA, or RIND) and (2) a new neurologic damage or 30 days mortality.Results Adverse cerebral outcomes occurred in 16 patients (1.4 percent). Nine patients had postoperative stroke, six suffered TIAs, and one had postoperative RIND.In multivariate analysis, older age (OR 1.07, 95% CI 1.01–1.14), congestive heart failure (OR 3.57, 95% CI 1.22–10.49) and prior stroke (OR 6.27, 95% CI 1.78–22.03) were significantly associated with increased risk of new neurologic damage. These parameters were also significantly associated with increased risk of the combined outcome (new neurologic damage/mortality).Conclusions A low incidence rate of adverse cerebral outcomes after CABG in community hospital can be achieved with the use of the suggested surgical intensive care, and anesthetic strategy. Advanced age, congestive heart failure, and prior stroke are associated with adverse outcomes.
Keywords: coronary artery bypass grafting; CABG; neurology/neurologic deficits; disease; injury; neurocognitive deficits